2007
DOI: 10.1007/s00702-007-0825-2
|View full text |Cite
|
Sign up to set email alerts
|

Very low frequency EEG oscillations and the resting brain in young adults: a preliminary study of localisation, stability and association with symptoms of inattention

Abstract: Initial evidence is provided for a pattern of VLFOs at rest which is associated with inattention symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 23 publications
5
60
1
Order By: Relevance
“…Direct current EEG (DC-EEG) was used to measure VLF oscillations as it has excellent temporal resolution and offers a more direct measure of neural activity than BOLD signals (Demanuele et al, 2013). The current study builds on previous research which has identified a robust resting state VLF EEG network with high spatial stabilitiy and temporal reliability (Helps et al, 2008). The intra-cranial sources of this network have been shown to overlap with the DMN identified using fMRI (Broyd et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…Direct current EEG (DC-EEG) was used to measure VLF oscillations as it has excellent temporal resolution and offers a more direct measure of neural activity than BOLD signals (Demanuele et al, 2013). The current study builds on previous research which has identified a robust resting state VLF EEG network with high spatial stabilitiy and temporal reliability (Helps et al, 2008). The intra-cranial sources of this network have been shown to overlap with the DMN identified using fMRI (Broyd et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…Initial studies suggest that VLF EEG oscillations (0.06-0.2 Hz) which are spatially and temporally stable have a spatial distribution across the scalp that corresponds in some ways to the DM network locations (i.e., frontal and posterior midline, Helps et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such data would provide useful information about the relationship between brain electrical oscillations and behaviour, a link that has been explored in the works by , Monto et al, (2008) and Helps et al (2008), and is fundamental for advances in the assessment of child psychiatric disorders (Rothenberger, 2009).…”
Section: Slow Wave Power and The Putative Link To Attentionmentioning
confidence: 99%
“…Particularly, very low frequency oscillations (VLFOs, <0.5 Hz) have been recorded in the EEG of preterm neonates, during epileptic seizure activity (Vanhatalo et al, 2005), in attention deficit hyperactivity disorder (ADHD) (Helps et al 2008(Helps et al , 2010, and during sleep stages (Steriade et al, 1993;Vanhatalo et al, 2004). These VLFOs, first observed by Biswal et al (1995) within the motor cortex in functional magnetic resonance imaging (fMRI) blood oxygenation level dependent (BOLD) signals during rest, appear to be intrinsically generated by the brain, are most prominent during rest and may allow temporal synchronisation to promote communication across diverse brain networks (Buzsáki and Draguhn, 2004;Fransson, 2005Fransson, , 2006.…”
Section: Introductionmentioning
confidence: 99%